Growth responses and photosynthetic characteristics of wild and phycoerythrin-deficient strains of Hypnea musciformis (Rhodophyta) - Yokoya, Nair S.; Necchi, Orlando; Martins, Aline P.; Gonzalez, Suzana F.; Plastino, Estela M. (Springer, 2007)
The phycoerythrin-deficient strain (green phenotype) of Hypnea musciformis (Rhodophyta) originated from a green branch, which had arisen as a spontaneous mutation in a wild plant (brown phenotype) collected from the Brazilian coast. The present study describes the growth responses to irradiance, photoperiod and temperature variations, pigment contents, and photosynthetic characteristics of the brown and green strains of H. musciformis. The results showed that growth rates increased as a function of irradiance (up to 40 mu mol photons m(-2) s(-1)) but, with further increase in irradiance (from 40 to 120 mu mol photons m(-2) s(-1)), became light-saturated and remained almost unchanged. The highest growth rates of the brown and green strains were observed in temperatures of 20-25 degrees C under long (14:10 h LD) and short (10:14 h LD) photoperiods. The brown strain had higher growth rates than the green strain in the short photoperiod, which could be related to the high concentrations of phycobiliproteins. Phycoerythrin was not detected in the green strain. The brown strain had higher concentrations of allophycocyanin and phycoerythrin in the short photoperiod while the green strain had higher concentrations of phycocyanin. The brown strain presented higher photosynthetic efficiency (alpha), and lower saturation parameter (I-k) and compensation irradiance (I-c) than the green strain. The brown strain exhibited the characteristics of shade-adapted plants, and its higher value of photosynthetic efficiency could be attributed to the higher phycoerythrin concentrations. Results of the present study indicate that both colour strains of H. musciformis could be selected for aquaculture, since growth rates were similar (although in different optimal light conditions), as the green strain seems to be adapted to higher light levels than the brown strain. Furthermore, these colour strains could be a useful experimental system to understand the regulation of biochemical processes of photosynthesis and metabolism of light-harvesting pigments in red algae.
Keywords: chlorophyll fluorescence; colour strains; growth; Hypnea musciformis; irradiance; photoperiod; photosynthesis; temperature